METODE PEMBELAJARAN KEWIRAUSAHAAN TRANSFORMATIF DI PERGURUAN TINGGI - Puji Riyanto (MAJALAH ILMIAH PEMBELAJARAN, 2010)
A strong country with progressive growth is own creative, innovative, flexibility of thingking, and capability to manage change of it’s people. Enterpreneurship education nowday is being concern of regulation show the goverment awareness as importance of it and try to integrate it into the curriculum. But, entrepreneurship education is tend to implement teoritically, similar to business school not as enterpreneuship school with abstract outcome. Learning methods are occur in conventional ways as transfer of knowledge process quite in much, so the attention to mindset and mental transformation is rarely happen. In the other side the learning models are lack of respect to practical knowledge. Project Based Learning (PBL) as an alternative learning model which is provide with sufficient learning outcomes through meaningfull learning process. University is closely relate to the workplace as a potential institution being a pioneer to implement PBL model that could gives both of practical and theoritical knowledge for the student. PBL as a model is relatively ideal to develop essential competences as learning outcomes, and simultaneously university can promote coorperate enterpreneurship to generate condusive environment in implementing PBL model as usefull context.